Pedagogical Leadership for Fostering Technology-Responsive Academic Supervision: A Multi-Site Study in Elementary Schools - Hartatik, Sri; Wijayanti, Wiwik (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study explores how pedagogical leadership fosters technology-responsive academic supervision to strengthen instructional quality and teacher professional learning in Indonesian elementary schools. Positioned within the context of educational transformation, the study conceptualizes academic supervision not merely as an administrative function but as a pedagogical strategy that encourages reflective teaching, instructional innovation, collaborative professional development, and responsiveness to technology-enhanced learning. A qualitative multi-site research design was employed across several public elementary schools in Pacitan Regency. Data were collected through in-depth interviews, participant observation, and document analysis involving school principals and teachers who actively participated in academic supervision practices. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing, while trustworthiness was ensured through source triangulation, methodological triangulation, and member checking. The findings reveal that pedagogical leadership strengthens technology-responsive academic supervision through three interrelated dimensions: establishing a shared instructional vision, managing instructional programs through systematic supervision, and cultivating a collaborative learning climate that supports teacher reflection and instructional innovation. Academic supervision was implemented through structured planning, classroom observation, reflective feedback, continuous professional coaching, and ongoing evaluation. These practices promoted teacher professionalism, strengthened collaborative learning communities, and encouraged adaptive instructional practices aligned with the demands of contemporary education. The study concludes that pedagogical leadership provides an essential foundation for integrating technology-responsive supervision into sustainable teacher development and improving instructional quality in elementary education.